2019
DOI: 10.25047/j-kes.v5i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Perilaku Ibu Tentang Gizi Seimbang Dengan Status Gizi Anak Tk Di DesaYosowilangun Lor Kabupaten Lumajang

Abstract: Pengetahuan gizi ibu menentukan semua yang dimakan oleh anak. Ibu yang memiliki pengetahuan gizi yang baik akan membentuk perilaku gizi seimbang yang baik untuk anak. Perilaku tersebut akan berpengaruh terhadap asupan zat gizi dan status gizi anak. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan perilaku ibu tentang gizi seimbang dengan status gizi anak TK di Desa Yosowilangun Lor Kabupaten Lumajang. Penelitian ini menggunakan metode survei analitik dengan desain studi cross sectional. Penel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
7
0
6
Order By: Relevance
“…The emo demo method uses imaginative and provocative methods to achieve changes in knowledge that make community behavior better in community health midwives. [4] The results showed that there were differences in the value of knowledge. This can be seen from the calculation of the Paired Samples Test which shows a significance value of 2 tailed indicating that there is a significant difference in respondents' knowledge after being given an intervention about feeding schedules in infants and children, p value = 0.000 with = 0.05.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The emo demo method uses imaginative and provocative methods to achieve changes in knowledge that make community behavior better in community health midwives. [4] The results showed that there were differences in the value of knowledge. This can be seen from the calculation of the Paired Samples Test which shows a significance value of 2 tailed indicating that there is a significant difference in respondents' knowledge after being given an intervention about feeding schedules in infants and children, p value = 0.000 with = 0.05.…”
Section: Resultsmentioning
confidence: 98%
“…Children's brain cells at this time are 90% developing, so nutritional adequacy is very influential at this time. [3] Toddlers who are not cared for will cause problems now and in the future [4,5] In fact, the growth and development of toddlers cannot be separated from obstacles in growth and development. Stunting is one of these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This research is in accordance with research conducted by Fadilah, et al, in 2017 in Yosowilangun Lor Village, Lumajang Regency, which shows that there is a relationship between maternal behavior regarding balanced nutrition and the nutritional status of children that most mothers have less behavior about balanced nutrition. Mother's behavior about balanced nutrition is getting less, hence, the child's nutritional status is getting lower (Fadila, et al, 2017) One of the factors that affect the nutritional status of children is the mother's behavior in choosing and providing food. The low mother's behavior can be caused by a lack of mother's level of knowledge about balanced nutrition and lack of ability to apply it in daily life.…”
Section: J the Relationship Of Mother's Actions To The Nutritional Status Of Toddlersmentioning
confidence: 99%
“…Beberapa penelitian telah dilakukan sebelumnya tentang pengaruh pengetahuan dengan gizi anak sekolah (Fajriani et al, 2020;Fadila et al, 2017;Couteau, 2020;Irnani & Sinaga;. Melihat data Riskesdas di Kota Makassar menunjukkan tingginya prevalensi kurang mengonsumsi sayur bagi anak usia sekolah maka peneliti ingin melihat hubungan antara pola makan dan pengetahuan mengenai gizi seimbang terhadap status gizi anak di Sekolah Dasar Islam Terpadu (SDIT) sekota Makassar yang diharapkan mampu mencakup banyak sampel dan lebih komprehensif.…”
unclassified